An Approach for Data Rate Maximization and Interference Mitigation in Massive MIMO Communication Systems Using SRPWGC-PD Algorithm - Poddar, Jaitashri; Subhashini, K. R. (Wireless personal communications, 2020)
Increasing usage of wireless communication systems and demand for higher data speed is appealing newer generations of cellular communication systems to provide higher data rate along with a reliable system, i.e. system which is free from interference. 5G Communication systems are believed to provide at least ten times betterment in area throughput, i.e. data rate by increasing the spectral efficiency. Massive MIMO (multiple-input multiple-output) is a key 5G technology that uses massive antenna arrays to provide a very high beamforming gain and spatial multiplexing of users and hence increases the spectral and energy efficiency. However, although Massive MIMO suppresses intra-cell interference and uncorrelated noise to a significant amount, it cannot mitigate the Pilot Contamination (PC) which is caused by reusing the same set of pilot signals in adjacent cells. In this paper, a new Pilot Decontamination (PD) technique, named as Softly Reused Pilot Weighted Graph Coloring-based Pilot Decontamination (SRPWGC-PD) has been introduced. In the proposed scheme, a scheme named soft pilot reusing is applied to separate the users in cells into two (inner and outer) zones, and then outer-zone users are allocated with orthogonal pilots; whereas a special pilot allocation scheme named weighted graph coloring algorithm is applied to the inner zone users to make generated PC as less as possible. Simulation and numerical analysis provide an insight that the proposed scheme outperforms in most of the performance indices, when compared to the existing schemes reported in the literature.